2022-RA-680-ESGO Safety and efficacy of MORAb-202 in patients with platinum-resistant ovarian cancer: results from the expansion part of a phase 1 trial in Japan. (20th October 2022) - Nishio, Shin; Yunokawa, Mayu; Matsumoto, Koji; Takehara, Kazuhiro; Hasegawa, Kosei; Hirashima, Yasuyuki; Kato, Hidenori; Ikezawa, Hiroki; Nomoto, Maiko; Hayato, Seiichi; Otake, Yohei; Miura, Takuma; et al.
Abstract : Introduction/Background: MORAb-202 is an antibody-drug conjugate consisting of farletuzumab (an antibody targeting folate-receptor alpha [FRα]) and eribulin mesylate (a microtubule dynamics inhibitor) conjugated via a cathepsin-B-cleavable linker. Antitumour activity was observed in the dose-escalation part of this phase 1 study; MORAb-202 0.9 mg/kg and 1.2 mg/kg Q3W were chosen for the expansion part of this study in patients with platinum-resistant ovarian cancer (PROC). Methodology: The primary objective for the expansion part of this phase 1 study was to define the safety and tolerability of MORAb-202. Secondary objectives included pharmacokinetic characterization and efficacy assessment (best overall response, ORR, PFS, and OS). Eligible patients had measurable disease per RECIST v1.1 and had ≤2 chemotherapy regimens after PROC diagnosis. The expansion phase began at the 0.9 mg/kg dose (Cohort 1); Cohort 2 (1.2 mg/kg) was initiated after a Cohort 1 safety assessment. Tumour responses were assessed per RECIST v1.1 by investigator. Results: Twenty-four patients were treated in Cohort 1; 21 patients were treated in Cohort 2. Grade ≥3 TEAEs occurred in 33.3% of patients in Cohort 1; 28.6% of patients in Cohort 2. The most common TEAE was interstitial lung disease (ILD)/pneumonitis at both dose levels (Cohort 1: 37.5% [n=9; 8 with grade 1, 1 with grade 2]; Cohort 2: 66.7% [n=14; 6 with grade 1, 7 with grade 2, 1 with grade 3]). Other common TEAEs of any grade are in table 1 . ORRs were 25.0% and 52.4% in Cohorts 1 and 2, respectively ( table 1 ). Antitumour activity was observed across FRα-expression levels (<50% and ≥50%) and will be presented. Conclusion: In the PROC population, antitumour activity was seen with MORAb-202 0.9 mg/kg and 1.2 mg/kg dosages. Despite small patient numbers, efficacy was observed irrespective of FRα-expression levels. ILD/pneumonitis (mostly low-grade) was the most common TEAE.